(untitled) - The World Bank in Vietnam (WB) (Ha Noi, 2004)
The overall objectives of the Rural Transport Project are to: a) improve and upgrade access to rural communities and link them to the district and provincial road networks; b) develop local capacity to improve the level of service of low-volume roads and to maintain them on a sustainable basis; and c) encourage the development of local contractors. To achieve the above objectives, the project will help finance the following main components: a) rural access road rehabilitation and maintenance using the spot improvement technique; b) institutional strengthening and training; and c) the study of issues relating to rural transport development.
Keywords: Rural transport,Giao thông nông thôn,Road building,Xây dựng đường bộ